2018
DOI: 10.14701/ahbps.2018.22.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Role of common bile duct resection in T2 and T3 gallbladder cancer patients

Abstract: Backgrounds/AimsRoutine bile duct resection as part of the typical oncological resection for patients with advanced gallbladder cancer remains controversial with regard to, ultimately, curative value. The aim of this study was to compare oncological outcomes for patients undergoing surgery for gallbladder cancer with or without bile duct resection.MethodsWe recruited, for the purpose of this study, all patients who underwent surgical resection for T2 and T3 gallbladder cancer at Severance hospital, Seoul, Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In patients without involvement of the CBD (for instance, based on cystic duct evaluation), there was no benefit for extrahepatic bile duct resection over ‘radical cholecystectomy’ in terms of overall survival, lymph node yield and recurrence rate, but associated morbidity was higher when the CBD was resected. Recent studies further showed no improvement in lymph node retrieval with resection of the CBD, and overall survival was worse. When adjusting for disease stage, survival was similar in patients undergoing CBD resection and those having no resection, suggesting that it is disease stage that drives the biology and thus the outcome, rather than extent of surgery.…”
Section: Resultsmentioning
confidence: 99%
“…In patients without involvement of the CBD (for instance, based on cystic duct evaluation), there was no benefit for extrahepatic bile duct resection over ‘radical cholecystectomy’ in terms of overall survival, lymph node yield and recurrence rate, but associated morbidity was higher when the CBD was resected. Recent studies further showed no improvement in lymph node retrieval with resection of the CBD, and overall survival was worse. When adjusting for disease stage, survival was similar in patients undergoing CBD resection and those having no resection, suggesting that it is disease stage that drives the biology and thus the outcome, rather than extent of surgery.…”
Section: Resultsmentioning
confidence: 99%
“…As such, the aim of this study was to evaluate the survival benefit of LND among patients with GBC based on the therapeutic index. Additionally, we sought to identify whether common bile duct (CBD) resection, which has been suggested as a means to achieve a more thorough LND, 14 provided any additional survival benefit in terms of the nodal therapeutic index.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the literature, patients who required additional bile duct resection had significantly higher blood loss, longer duration of surgery and postoperative hospital stay, and increased risk of postoperative morbidity [ 19 , 20 ]. In the present study, positive CDM requiring EHBD resection had significantly higher intraoperative blood loss (375 vs. 200 ml, p=0.026) and longer hospital stay (11.5 vs. five days, p=0.002), while postoperative morbidity was comparable (p=0.722).…”
Section: Discussionmentioning
confidence: 99%